Property Relations Between Unmarried Cohabitants in International Family Law - Pashynskyi, Anatoliy (Teisė, 2020)
This article is about the legal regulation of property relations between unmarried cohabitants in national legislation and the attempts to govern the said issues on the international level. The paper classifies states into groups based on their legal approach to unmarried cohabitation with examples from domestic legislation and court practice. The paper highlights the problem of absence of international conventions and national conflict of law rules on the matter and offers solutions to these issues.
Keywords: international family law; unmarried cohabitation; property relations; conflict of laws; de facto unions